Correlations between perturbation theory and power corrections in QCD at zero and finite temperature - Megías Fernández, Eugenio; Ruiz Arriola, Enrique; Salcedo, L. L. (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
The duality between QCD perturbative series and power corrections recently conjectured by Narison and Zakharov is analyzed. We propose to study correlations between both contributions as a diagnostics tool. A very strong correlation between perturbative and nonperturbative contributions is observed for several observables at zero and at finite temperature supporting the validity of the dual description.